Comparative Analysis of Complete Chloroplast Genome and Phenotypic Characteristics of Japanese Apricot Accessions - Daouda Coulibaly; Xiao Huang; Shi Ting; Shahid Iqbal; Zhaojun Ni; Kenneth Omondi Ouma; Faisal Hayat; Wei Tan; Guofeng Hu; Chengdong Ma; Benjamin Karikari; Mahmoud Magdy; et al. (Horticulturae, 2022)
Japanese apricot (Prunus mume Sieb. et Zucc.) is among the most valued fruits and flowering plants in eastern Asia. However, few comparative studies have been conducted with respect to its agro-morphological and pomological traits, chloroplast (cp) genome sequences and plastid diversity. Therefore, a comparative study was, conducted to investigate the divergence and geographic distribution of ten Japanese apricot accessions from three Chinese provinces (Zhejiang, Jiangsu and Sichuan). Phenotypic characteristics of the evaluated accessions, such as leaf length, tip leaf length, flower diameter, anther number, fruit weight, longitudinal height, transversal height, lateral height, fruit stone weight, stone longitudinal height, stone transversal height, stone lateral heigh, titratable acid content and total soluble solids, varied significantly (p < 0.05) among the ten investigated accessions. On the other hand, most of the investigated accessions were statistically similar within the same province. Comparing the Cp genomes of P. mume accessions with those of the genus Prunus revealed a similarity in structure and composition with slight differences. “Bayes empirical Bayes” (BEB) analysis in Prunus species, including P. mume, revealed BEB in rps16, rps3, rpoC1(4*), rpl32, rpl16, rbcL, psbF, petB, ndhF, clpP and ccsA genes. The BEB value of the rpoC1 gene is higher than 0.95, indicating that it is potentially under positive selection. Interestingly, the accessions from the same province of origin had the same number of forward repeat sequences. Furthermore, all accessions from Zhejiang province had the same number of simple sequence repeats. Similarly, nucleotide deletion/insertion of the ycf1 sequence and the results of phylogenetic trees revealed that accessions were mainly clustered according to their province of origin. Our comparative study of agronomical traits, chloroplast composition, structure, nucleotide variability of cp genome and phylogeography in Japanese apricot accessions provides valuable information on their diversity and geographic distribution.